Integrating federated information sources through the use of ontologies - Buccella, Agustina (2004)
Ontologies serve as a mean to establish a conceptually concise basis for communicating knowledge for many purposes. Within the information integration area, ontologies are useful to solve heterogeneity problems. They provide a set of knowledge terms, including the vocabulary, the semantic interconnections and some simple rules of inference and logic. In this paper we present a helpful method to integrate a new data source into a federated system taking advance of the use of ontologies.